2017
DOI: 10.3389/fpsyg.2017.01001
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Picture Perception: Repetition Effects in Free-Viewing and during an Explicit Categorization Task

Abstract: Several studies have found that, despite a decrease in the overall amplitude of the late positive potential (LPP) with repeated presentation of the same picture, emotional stimuli continue to elicit a larger LPP than neutral ones. These findings seem to support the hypothesis that the affective modulation of the LPP reflects a mandatory process and does not rely on stimulus novelty. However, in these studies participants were asked to merely look at the pictures, without carrying out any additional task (free-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 64 publications
4
21
0
Order By: Relevance
“…The images’ contexts are positive (e.g., pictures of erotic or romantic couples), neutral (e.g., portraits or images of multiple people in an everyday context), or negative (e.g., photos of mutilated bodies or violence). We balanced these emotional categories and ensured that they did not differ in terms of arousal, based on the results of a previous psychophysiological study [92]. We uniformly allocated the picture exemplars such that there were 84 images in each of the positive, neutral, and negative categories.…”
Section: Methodsmentioning
confidence: 99%
“…The images’ contexts are positive (e.g., pictures of erotic or romantic couples), neutral (e.g., portraits or images of multiple people in an everyday context), or negative (e.g., photos of mutilated bodies or violence). We balanced these emotional categories and ensured that they did not differ in terms of arousal, based on the results of a previous psychophysiological study [92]. We uniformly allocated the picture exemplars such that there were 84 images in each of the positive, neutral, and negative categories.…”
Section: Methodsmentioning
confidence: 99%
“…An advantage of this paradigm is that repeated presentation reduces stimulus novelty (Öhman,1992; Siddle and Spinks, 1992; Kahneman, 1973), which may allow for motivational effects to emerge more clearly. Several studies consistently showed that even after massive repetition, pleasant and unpleasant cues continue to elicit larger EPNs and LPPs compared to neutral ones, a result suggesting that, also when the images are no longer novel, affectively engaging pictures to continue to activate mental representations with strong associations to motivational circuits (Bradley et al, 2006; Codispoti et al, 2007; Ferrari et al, 2011; Ferrari et al, 2017; Mastria et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…LPP is an important indicator for late emotional arousal and can dynamically reflect individual subjective emotional changes (Cuthbert et al, 2000; Mastria et al, 2017). A comparison with the LPP amplitude of the participants under 400–500, 500–600, 600–700, and 700–800 ms time windows showed that the main effect of the time window was significant, which indicated that late emotional arousal followed a dynamic changing process.…”
Section: Discussionmentioning
confidence: 99%
“…LPP is an important index with which to measure the level of late emotional arousal, and the maximum value generally appears after stimulus presentation for 400 ms (Hajcak and Nieuwenhuis, 2006; Foti and Hajcak, 2009). A number of studies have shown that LPP is an important index to measure emotional regulation, and more negative emotions after adjustment will lead to lower LPP amplitudes (Hajcak and Nieuwenhuis, 2006; Moser et al, 2006; Krompinger et al, 2008; Moser et al, 2009, 2010; Thiruchselvam et al, 2011; Mastria et al, 2017). Based on these results, we hypothesized that individuals with a low social status will have more negative LPP amplitudes for hedonic product information than for utilitarian product labels, while high-social-status individuals will not show this difference.…”
Section: Introductionmentioning
confidence: 99%